Season of birth : a study of schizophrenia and other mental disorders - Dalen, Per (North-Holland Pub. Co. : American Elsevier, 1975)
Season of Birth: A Study of Schizophrenia and Other Mental Disorders discusses the correlation between season of birth and mental disorders. The book provides reviews of studies relevant to understanding how the season of birth relates to various mental disorders. The first five chapters cover pregnancy and birth related issues. These chapters cover vital statistics, obstetrics, and neonatal and congenital abnormalities and disorders. The next two chapters deal with intelligence and mental disorders, respectively. Chapters 8 to 12 discuss the studies done on Swedish and South African demograph.